Validation of the Chinese Non‐pharmacological Therapy Experience Scale in persons with intellectual disability - Lily Yuen Wah Ho; Kenny Chi Wing Chin; Connie Yuen Yee Fung; Claudia Kam Yuk Lai (Wiley, 2020)
Abstract Aim To validate the 4‐ and 7‐point Chinese Non‐pharmacological Therapy Experience Scales and test the psychometric properties of the scales on persons with intellectual disability. Design A validation study. Methods Sixty‐seven persons with intellectual disability were recruited from six hostels or centres for persons with intellectual disability in Hong Kong. A total of 1,163 and 1,161 observations were collected by the trained observers with the 4‐point and 7‐point scales, respectively. The floor and ceiling effects, inter‐rater reliability, internal consistency, responsiveness of both scales and the scale equivalence were examined. Results The Cronbach's α of the 4‐ and 7‐point scales was .762 and .797, respectively. The correlation between the two scales was 0.906. The inter‐rater reliability of the 4‐ and 7‐point scales was 0.774 and 0.835, respectively. Neither scale had the floor or ceiling effects. The effect size of the 7‐point scale was consistently higher than that of the 4‐point scale.